Impact of age on surgical staging and approaches (laparotomy, laparoscopy and robotic surgery) in endometrial cancer management. Issue 4 (April 2017) - Bourgin, C.; Lambaudie, E.; Houvenaeghel, G.; Foucher, F.; Levêque, J.; Lavoué, V.
Abstract: Objective: This study aims to evaluate the different surgical approaches, perioperative morbidity and surgical staging according to age in patients with endometrial cancer. Methods: Multicentre retrospective study. Cancer characteristics and perioperative data were collected for patients surgically treated for endometrial cancer. The patients were divided into 2 groups according to their age: younger or older than 75 years. Results: Surgery was performed on 270 women <75 years old and on 74 ≥ 75 years old. Minimally invasive surgery was performed less often in the elderly compared with their younger counterparts (58.2% vs. 74.8%; p = 0.006). Independently of the surgical approach, the rate of pelvic and para-aortic lymphadenectomy was lower in women older than 75 years old than their younger counterparts (52.7% vs. 74.8%; p < 0.001; 8.1% vs. 21.8%; p = 0.007 respectively). According to the guidelines, more frequent surgical understaging was seen in the elderly compared with the younger (37% vs. 15.2%; p = 0.002). In the comparison of complications for each surgical approach, there was no statistical difference in the ≥75-year-old age group in terms of intra- or postoperative complications between the laparotomy, laparoscopy or robotic surgery group. We found a shorter length of hospital stay for the women who underwent laparoscopy or robotic surgery compared with laparotomy (p < 0.0001). Conclusion: Elderly women with endometrial cancer are often surgically understaged whereas there is no evidence of greater perioperative complications than for their younger counterparts. They should benefit from minimally invasive surgery and optimal surgical staging to the same extent as younger women.